Development of a novel stability indicating RP-HPLC method for quantification of Connexin43 mimetic peptide and determination of its degradation kinetics in biological fluids - Rohit Bisht; Ilva D. Rupenthal; Sreevalsan Sreebhavan; Jagdish K. Jaiswal (Elsevier, 2017)
Connexin43 mimetic peptide (Cx43MP) has been intensively investigated for its therapeutic effect in the management of inflammatory eye conditions, spinal cord injury, wound healing and ischemia-induced brain damage. Here, we report on a validated stabilityâindicating reversed-phase high performance liquid chromatography (RP-HPLC) method for the quantification of Cx43MP under stress conditions. These included exposure to acid/base, light, oxidation and high temperature. In addition, the degradation kinetics of the peptide were evaluated in bovine vitreous and drug-free human plasma at 37Â Â°C. Detection of Cx43MP was carried out at 214Â nm with a retention time of 7.5Â min. The method showed excellent linearity over the concentration range of 0.9â250Â Âµg/mL (R2 â¥ 0.998), and the limits of detection (LOD) and quantification (LOQ) were found to be 0.90 and 2.98Â Î¼g/mL, respectively. The accuracy of the method determined by the mean percentage recovery at 7.8, 62.5 and 250Â Âµg/mL was 96.79%, 98.25% and 99.06% with a RSD of < 2.2%. Accelerated stability studies revealed that Cx43MP was more sensitive to basic conditions and completely degraded within 24Â h at 37Â Â°C (0% recovery) and within 12Â h at 80Â Â°C (0.34% recovery). Cx43MP was found to be more stable in bovine vitreous (t1/2slow= 171.8Â min) compared to human plasma (t1/2slow = 39.3Â min) at 37Â Â°C according to the two phase degradation kinetic model. These findings are important for further pre-clinical development of Cx43MP. Keywords: Connexin43 mimetic peptide, RP-HPLC, Stress degradation, Peptide stability, Bovine vitreous, Human plasma